KETERAMPILAN MEMBERIKAN VARIASI MENGAJAR MAHASISWA PPL PRODI PAI FAKULTAS TARBIYAH ILMU KEGURUAN UIN SYEKH M. DJAMIL DJAMBEK BUKITTINGGI DALAM PERSEPSI GURU PAMONG DI PONDOK PESANTREN MADINATUL MUNAWWARAH BUKITTINGGI - Syafrudin; Muhiddinur Kamal; Wedra Aprison; Salmi Wati (KOLONI, 2022)
This research was motivated by the fact that it was not known how the civil servant teacher's perspective on the teaching skills carried out by PPL students of the Islamic Religious Education Study Program Faculty of Tarbiyah Teacher Training UIN Sheikh M. Djamil Djambek Bukittinggi in 2017-2019 at Pondok Pesantren Madinatul Munawwarah Bukittinggi. The type of research used in this research is descriptive qualitative research and is located in Pondok Pesantren Madinatul Munawwarah Bukittinggi, the data collection technique used is interview. Data analysis used the Milles and Hubberman models, namely data reduction, data analysis, and drawing conclusions/verification. The results showed that the skills of varying the learning carried out by PPL students of the Department of Islamic Education, Faculty of Tarbiyah Teacher Science UIN Sheikh M. Djamil Djambek Bukittinggi both in terms of varying teaching styles, interaction patterns, use of media, learning methods and others were good and already fulfill the provisions in varying learning, although there are still those who have not perfectly applied it in learning so that learning seems monotonous and boring.  Keywords: Teachers' Perceptions, Teaching Skills, PPL Students, Department of Islamic Education